2018
DOI: 10.1016/j.eneco.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

How shifting investment towards low-carbon sectors impacts employment: Three determinants under scrutiny

Abstract: The threat of climate change requires redirecting investment towards low-carbon sectors, and this shift generates heated debates about its impact on employment. Many studies exist, most of which use CGE or Input-Output (IO) models. However, the economic mechanisms at play remain unclear. This paper disentangles the channels of job creation and studies to what extent the results of simpler IO models diverge from CGE results.Using stylized models, we show that a shift in investment creates jobs in IO if it promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…As a result, the models ignore adjustment effects. Input-output analyses do, however, offer a clear picture of which sectors will be most affected under each scenario (Perrier and Quirion, 2018). In addition, the simulations here are based on the assumption that labor productivity grows similarly in all sectors, following projections from the OECD (Guillemette and Turner, 2018).…”
Section: Insights Not Predictionsmentioning
confidence: 99%
“…As a result, the models ignore adjustment effects. Input-output analyses do, however, offer a clear picture of which sectors will be most affected under each scenario (Perrier and Quirion, 2018). In addition, the simulations here are based on the assumption that labor productivity grows similarly in all sectors, following projections from the OECD (Guillemette and Turner, 2018).…”
Section: Insights Not Predictionsmentioning
confidence: 99%
“…Using a panel dataset of 80 countries, [56] find positive impact of renewable energy consumption on unemployment in European Union and Africa while negative in Asia and Latin American countries. [57] describe the existence of three economic channels for job creation, so that a shift in investment towards renewables increases employment if it targets sectors with a higher share of labour compensation out of value added, lower wages or lower import rates. The authors found positive employment impacts arising from weatherproofing and solar panels, a result that is robust across models used in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an alternative to input-output (IO) models, computable general equilibrium (CGE) models are also used to estimate employment impacts of technological change Perrier and Quirion (2018). estimate the employment impact of investing in low-carbon sectors in France using both IO and CGE models.…”
mentioning
confidence: 99%